RAGAM KERUANGAN TEPI SUNGAI DI KAWASAN PERMUKIMAN PRODUKTIF ALALAK, BANJARMASIN - , ANNISA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Banjarmasin as a riversides city which showed a development of citis with industrial, services and trade activites increased quite rapidly by utilizing the river network. The development of industry and infrastructure that it used by the people of the Alalak Tengah dan Alalak Selatan riversides to earn additional income by making use their residences as the place of production or other business support without regard to the feasibility of settlements. It caused the spatial structure changes following the existing conditions and gave rise to the type of spatial diversity on that areas. Timber production industry in Alalak Tengah and Alalak Selatan areas is a generator of the settlements development term of quality and quantity in order to improving socio economic conditions. But also provided another impact to other that not less important, the occurrences of rapid settlements growth and uncontrolled, resulting in irregularity and the decline of environment quality and riversides settlements. The research used rasionalistic approach with qualitative methods. Rasionalistic approach using a grand theory based on the research parameters, variable and indicators of the riversides settlements pattern area that can be explained by the solid/void and circulation networks as well as activities support of the productive settlements in Alalak Tengah and Alalak Selatan riversides area. The results of the research mentions that there are 3 types of productive settlements (typology/spatial diversity) in Alalak Tengah and Alalak Selatan riversides area besed on the land use or area function, solid/void, circulation networks, and activities support of the existing area, that is the land productive settlements area type, the riverside productive settlements area type, and the river productive settlements area type. The recommendations of the research are directed to the guidelines of Alalak Tengah and Alalak Selatan in accordance with the land use of the region as riverside productive settlements area.